A Prospective Pilot Study of Anxiety Sensitivity and Adolescent Sports-Related Concussion. (14th December 2020) - Caze, Todd; Vásquez, Desi; Moffatt, Kody; Waple, Kerry; Hope, Debra
Abstract: Objective: This study examined the relationship of that anxiety sensitivity (AS) with the initial and ongoing symptoms reported by adolescents after sustaining a sports-related concussion (SRC). Method: Participants were 40 adolescents, ages 13–18, presenting for treatment at a children's sports medicine specialty clinic following a diagnosis of either an SRC or a musculoskeletal injury. After the initial clinic intake, participants completed an online survey at three-time points. Survey measures included the self-report graded symptom checklist and the AS Index-3. Researchers used growth curve analysis to examine the relationship between AS Index-3 scores with initial and ongoing symptom reporting over time. The 20 participants sustaining an SRC were matched by age, gender, and race with 20 musculoskeletal injury controls. Results: Concussed adolescents with higher AS scores reported more initial symptoms than did those reporting musculoskeletal injury. AS was not related to the rate of symptom reduction over time for either group. Conclusion: Higher AS moderated the relationship between injury type (concussion vs. musculoskeletal injury) and the total number of initial symptoms reported by adolescent participants, with every unit increase in AS yielding a four-unit increase in initial symptoms reporting. Previous research has shown that elevated initial symptom scores are a strong predictor of protracted recovery in concussion. AS is amenable to brief treatment interventions. It is a potential early target for treatment intervention following diagnosis of adolescent SRC.